Comparative Study of Ferroelectric and Piezoelectric Properties of BNT-BKT-BT Ceramics near the Phase Transition Zone - Fernandez-Benavides, David Andres (Materials (Basel), 2018)
We report a comprehensive comparative study of ferroelectric and piezoelectric properties of BNT-BKT-BT ceramics through the MPB (morphotropic phase boundary) zone, from the rhombohedral to the tetragonal phases in the system (97.5−x)(Bi(0.5)Na(0.5))TiO(3) + x(Bi(0.5)K(0.5))TiO(3) + 2.5(BaTiO(3)), where x = 0 to 24.5 mol %. The structural transitions were studied by XRD patterns and Raman spectra. The MPB was confirmed between x = 10 and 12.5 mol % BKT. The dielectric/ferroelectric/piezoelectric properties of the BNT-BKT-BT system are maximized in the MPB region exhibiting a dielectric constant of 1506, a remanent polarization of 34.4 μC/cm(2), a coercive field = 36.9 kV/cm, and piezoelectric values of d(33) = 109 pC/N, k(t) = 0.52, and k(p) = 0.24. Changes in microstructure as a function of BKT content are also presented and discussed.